On s-g-cocompact open set and Continuity - Al-Abdulla, Raad; Jabar, Salam (Al-Qadisiyah Journal of Pure Science, 2020)
Throughout this paper by a space we mean a supra topological space, we have studied some of propertiese to new set is called supra generalize- cocompact open set ( -g-coc-open set)and find the relation with other sets and our concluded anew class of the function called -g-coc-continuous, -g-coc’-continuous, -coc-continuous, -coc’-continuous We shall provided some properties of these concepts and it will explain the relationship among them and some results on this subjects are proved Throughout this work , and new concept have been illustrated including , -coc-ompact space .